Use of intra-urethral steroid clobetasol cream to prevent the recurrence of urethral stricture after optical urethrotomy: Randomized clinical trial - Ahmed, M; Hossain, SM; Islam, MT; Kobir, G; Basu, BK (Mediscope, 2019)
Background: One of the most frequently used treatments of urethral strictures is the optical internal urethrotomy (OIU). About 20%-60% of urethral stricture patients develop recurrent stricture after Urethrotomy. Glucocorticoids have proved anti-proliferative effect and thereby used to reduce the formation of scar tissue. In urethral stricture, the main pathology is scar tissue formation. Objective: The aim of this study is to see the influence the local application of steroid clobetasol cream after Urethrotomy. Method: Between January to December 2016, all Bulbar urethral stricture patients attended to the hospital and private clinics, were included in this study. They were placed in two groups alternatively. They underwent standard OIU. First group (35 patients) offered clean intermittent self-catheterization (CISC) postoperatively without any steroid cream in urethra. The second group (35 patients) practiced CISC in the same way but used clobetasol cream with catheter. Both groups used topical anaesthesic Lidocain HCL for lubrication of urethra. Result: No patient developed recurrence with clobetasol cream after 3 months, but two patients developed recurrence without steroid. At 6 months, this result is 6 (17.14%) and 10 (28.57%) accordingly. Conclusion: Topical steroid clobetasol cream reduces urethral stricture recurrence. Mediscope Vol. 6, No. 2: Jul 2019, Page 59-63